2020
DOI: 10.1093/nar/gkaa827
|View full text |Cite
|
Sign up to set email alerts
|

ERH facilitates microRNA maturation through the interaction with the N-terminus of DGCR8

Abstract: The microprocessor complex cleaves the primary transcript of microRNA (pri-miRNA) to initiate miRNA maturation. Microprocessor is known to consist of RNase III DROSHA and dsRNA-binding DGCR8. Here, we identify Enhancer of Rudimentary Homolog (ERH) as a new component of Microprocessor. Through a crystal structure and biochemical experiments, we reveal that ERH uses its hydrophobic groove to bind to a conserved region in the N-terminus of DGCR8, in a 2:2 stoichiometry. Knock-down of ERH or deletion of the DGCR8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 62 publications
(88 reference statements)
1
55
0
Order By: Relevance
“…Finally, the human ERH homolog has recently been shown to support the microprocessor complex during microRNA (miRNA) processing (Fang and Bartel 2020; Hutter et al 2020; Kwon et al 2020). Microprocessor is a trimeric complex consisting of one copy of DROSHA and two copies of DGCR8 and dimerization of DGCR8 is necessary for miRNA processing (Faller et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the human ERH homolog has recently been shown to support the microprocessor complex during microRNA (miRNA) processing (Fang and Bartel 2020; Hutter et al 2020; Kwon et al 2020). Microprocessor is a trimeric complex consisting of one copy of DROSHA and two copies of DGCR8 and dimerization of DGCR8 is necessary for miRNA processing (Faller et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…S4D). PID-3 pep shows well-ordered electron density for residues 177-193 (Chain C) and [179][180][181][182][183][184][185][186][187][188][189][190][191][192][193] and occupies a similar surface on ERH as DGCR8 in the human ERH/DGCR8 peptide complex (Kwon et al 2020), and Mmi1 in the fission yeast Erh1/Mmi1 peptide complex (Xie et al 2019) (Supplemental Fig. 4A).…”
Section: Structural Insights Into the Formation Of The Erh-2/pid-3 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…A second model would involve protein cofactors able to recruit the Microprocessor on the neighboring miRNA hairpin. Very recently, it was shown that ERH and SAFB2 can interact with the Microprocessor and their ability to dimerize may even mediate multimerization of the Microprocessor and allow its simultaneous binding to several hairpins (35, 38, 40, 44). However, this model remains to be clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Maturation of pri-miRNAs by the Microprocessor is controlled by sequence and structural features of miRNA hairpin, defining the basal level of pre-miRNAs excised (see (34) for a recent review). Recently, several studies demonstrated interdependent processing in the context of bicistronic pri-miRNA where an optimal miRNA hairpin assists the processing of a neighboring suboptimal one (3540). Such interdependency has not yet been documented in the case of larger miRNA clusters.…”
Section: Introductionmentioning
confidence: 99%